Clinical diversity in glycogenosis type II. Biosynthesis and in situ localization of acid alpha-glucosidase in mutant fibroblasts. - Reuser, A J (1987)
The molecular basis of clinical diversity in glycogenosis type II (Pompe's disease) was investigated by comparing the nature of acid alpha-glucosidase deficiency in cultured fibroblasts from 30 patients. Biosynthetic forms of acid alpha-glucosidase with different molecular mass were separated electrophoretically and identified by immunoblotting. Immuno-electron microscopy was employed to determine the intracellular localization of mutant enzyme. Our studies illustrate that maturation of acid alpha-glucosidase is associated with transport to the lysosomes. Deficiency of catalytically active mature enzyme in lysosomes is common to all clinical phenotypes but, in the majority of cases, is more profound in early onset than in late onset forms of the disease. Thus, the results suggest that the clinical course of glycogenosis type II is primarily determined by the amount of functional acid alpha-glucosidase. The role of secondary factors can, however, not be excluded because three adult patients were identified with very low activity and little enzyme in the lysosomes.